Trophic ecology and resource partitioning of Haemulidae species along the Northeastern Brazilian continental shelf - Limeira, Ádamo Gabriel Cavalcanti; Frédou, Thierry; Soares, Andrey Paulo Cavalcanti; Lira, Alex Souza; Le Loc´h, François; Viana, Girlene Fábia Segundo; Rosa-Filho, José Souto; Munaron, Jean Marie; Lucena-Frédou, Flávia (Neotropical Ichthyology, 2022)
Abstract In the Southeastern Tropical Atlantic, Haemulidae family play an important role both environmentally, acting as a link between lower and higher trophic levels, and socioeconomically, being widely caught by artisanal fleets. This study aimed to describe the trophic ecology of three grunt species (Haemulon aurolineatum, H. plumierii and H. squamipinna) considering spatial, temporal and ontogenetic aspects, integrating stomach content and stable isotopes analysis. Sampling occurred in 26 stations along the Northeast of Brazil (04°– 09°S), in August 2015 and April 2017, using bottom trawling net. There was greater feeding intensity at night, at latitudes below 08°S and in the inner continental shelf. Higher values of δ¹⁵N were reported for H. aurolineatum and H. plumierii collected near coastline. The isotopic niche breadth indicated that H. aurolineatum has a narrower diet thanH. plumierii. For the three species, the trophic level ranged between three and four. Considering stomach content and isotopic niche, diet was similar comparing species. This trophic ecology pattern reveals a likewise use of the habitat, which may be essential for identifying priority areas for conservation on an ecosystem basis, especially in rich reef zones that are subject to several increasing pressures, such as those in Northeast Brazil. Resumo No Atlântico Tropical Sudeste, peixes da família Haemulidae desempenham um papel importante tanto ambientalmente, atuando como um elo entre os níveis tróficos mais baixos e mais altos, quanto socioeconomicamente, sendo amplamente capturados pelas frotas artesanais. Este estudo teve como objetivo descrever a ecologia trófica de três espécies de roncadores (Haemulon aurolineatum, H. plumierii e H. squamipinna) considerando aspectos espaciais, temporais e ontogenéticos integrando conteúdo estomacal e análise de isótopos estáveis. A amostragem ocorreu em 26 estações ao longo do Nordeste do Brasil (04°– 09°S), em agosto de 2015 e abril de 2017, utilizando rede de arrasto de fundo. Houve maior intensidade de alimentação à noite, em latitudes abaixo de 08°S e na plataforma continental interna. Valores mais altos de δ¹⁵N foram reportados para H. aurolineatum e H. plumierii coletados perto da linha costeira. A amplitude do nicho isotópico indicou que o H. aurolineatum tem uma dieta mais estreita do que o H. plumierii. Para as três espécies, o nível trófico variou entre três e quatro. Considerando o conteúdo estomacal e o nicho isotópico, a dieta foi semelhante comparando as espécies. Este padrão de ecologia trófica mostra um uso semelhante do habitat, que pode ser essencial para identificar áreas prioritárias para conservação em uma base ecossistêmica, especialmente em zonas ricas de recifes que estão sob várias pressões crescentes, como as do Nordeste do Brasil.